Extramedullary malignant melanotic schwannoma of the spine: Case report and an up to date systematic review of the literature. (November 2020) - Solomou, Georgios; Dulanka Silva, Adikarige Haritha; Wong, Adrianna; Pohl, Ute; Tzerakis, Nikolaos
Abstract: Background: Melanotic schwannoma is a rare variant of schwannoma. Extramedullary melanotic schwannoma originates in the vicinity of nerve roots mimicking other intervertebral disc disorders. Therefore, T1 and T2-weighted MRI sequences become an essential tool for diagnosis. Aside from case reports, no large studies exist to provide consensus on the signal intensities in T1 and T2-weighted MR imaging. Moreover, no clear evidence is available to delineate prognosis. Here, a case report is presented together with a subsequent systematic review of the literature regarding this rare entity. Case description: A 45-year old female presented with a one-year history of insidious onset of neck pain and paraesthesia. Magnetic resonance imaging confirmed an extramedullary lesion along the C6 nerve root with T1-weighted hyperintensity and T2-weighted hypointensity. Despite two surgical decompressions and adjuvant immunotherapy, the patient unfortunately passed away due to metastatic progression. Discussion: According to the systematic review conducted, in over half of the cases of extramedullary melanotic schwannoma, there is local reoccurrence and/or distal metastasis. Moreover, in 64.7% and 70.6% of the cases, the T1-weighted image of the lesion appears hyperintense and hypointense on a T2-weighted image, respectively. It is an aggressive variant of schwannoma, one of the most commonly observed extramedullary tumours presenting to neurosurgical practice. Conclusion: Our results highlight that specific T1 and T2-weighted imaging findings can provide valuable information, enabling early suspicion, influencing the surgical aims and strategy and the timely commencement of relevant immunotherapy. Considering the poor prognosis, early adjuvant therapy with other modalities should be considered. Highlights: Up to date review collating evidence regarding local recurrence/metastasis and MR imaging findings unique for the melanotic schwannoma. The lesion appears hyperintense and hypointense on a T1-weighted and T2-weighted magnetic resonance imaging, respectively. In over half of the cases, there is local recurrence and distal metastasis thus a radical excision is recommended early on. Neurosurgeons should embrace discussion with oncologist for early adjuvant therapy.